2021
DOI: 10.1111/cei.13584
|View full text |Cite
|
Sign up to set email alerts
|

Gingival transcriptomics of follicular T cell footprints in progressing periodontitis

Abstract: Summary Follicular helper T cells (Tfh) cells have been identified in the circulation and in tertiary lymphoid structures in chronic inflammation. Gingival tissues with periodontitis reflect chronic inflammation, so genomic footprints of Tfh cells should occur in these tissues and may differ related to aging effects. Macaca mulatta were used in a ligature‐induced periodontitis model [adult group (aged 12–23 years); young group (aged 3–7 years)]. Gingival tissue and subgingival microbiome samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…A striking feature of the AMF gene expression patterns was exposed when examining the clustering of the AMF expression in gingival tissues from the various age groups, and in health and disease. Our previous results have supported that the transition from health to disease was a major driving feature of altered gingival gene expression patterns for multiple pathways [27,30,37,38,40,41,[58][59][60][61][62]. While some age differences were observed, the major changes appeared to be disease related.…”
Section: Discussionsupporting
confidence: 56%
“…A striking feature of the AMF gene expression patterns was exposed when examining the clustering of the AMF expression in gingival tissues from the various age groups, and in health and disease. Our previous results have supported that the transition from health to disease was a major driving feature of altered gingival gene expression patterns for multiple pathways [27,30,37,38,40,41,[58][59][60][61][62]. While some age differences were observed, the major changes appeared to be disease related.…”
Section: Discussionsupporting
confidence: 56%
“…Pre-clinical studies on periodontal diseases in non-human primates mostly use a ligature-induced periodontitis protocol in Macaca mulatta. To the best of our knowledge there is not documented subsequent development of neuropsychiatric symptoms in these animals with periodontitis; however, recent data have shown that this ligature model induces an increase in follicular helper T cell (Tfh) responsiveness during the progression of periodontitis, which was found to be affected by age and the specific microbial complexes present in the oral microbiome (79). Follicular helper T cells are a specialized subset of CD4+ T cells that play a critical role in protective immunity helping B cells produce antibodies against foreign pathogens.…”
Section: Findings In Non-human Primatesmentioning
confidence: 99%
“…8c ). Few papers have described oral tertiary lymphoid structures as a common feature in periodontitis 48 , 49 . We quantified this by the same ROIs using single protein markers and manual thresholding to determine the positivity of by converting 0-255 auxiliary units of fluorescence to a binary classification of either negative (“0”) or positive (“1”; see: Methods).…”
Section: Resultsmentioning
confidence: 99%